1995
DOI: 10.1159/000111295
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death Enhances Uniformity in Rat Cerebral Hemispheres

Abstract: Programmed cell death (apoptosis) in rat cerebral hemispheres (CH) reportedly occurs around postnatal day 7 and kills 15–75% of all cells whose continuing presence would be of disadvantage for the organism: neurons erroneously connected, or supranumerary neurons that do not find targets and are not protected by neurotrophins. In the present paper we report that apoptosis (or a concomitant phenomenon) reduces also variability (coefficient of variation, CV) of CH parameters: weight, DNA content and protein conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…17 Apoptosis has been thought to reduce the variability (in weight and in DNA and protein content) of cerebral hemispheres in the rat during early postnatal development. 21 A study of embryonic and postnatal mice showed apoptosis of proliferative neuroblasts in the cerebral cortex and discussed a possible correlation between the start of differentiation and the beginning of apoptosis. 10 It is notable that this latent peak in apoptosis is coincident with the distribution of apoptotic profiles in white matter regions and in cells that either presumably failed to migrate from the subplate or are radial glia.…”
Section: Neocortexmentioning
confidence: 99%
“…17 Apoptosis has been thought to reduce the variability (in weight and in DNA and protein content) of cerebral hemispheres in the rat during early postnatal development. 21 A study of embryonic and postnatal mice showed apoptosis of proliferative neuroblasts in the cerebral cortex and discussed a possible correlation between the start of differentiation and the beginning of apoptosis. 10 It is notable that this latent peak in apoptosis is coincident with the distribution of apoptotic profiles in white matter regions and in cells that either presumably failed to migrate from the subplate or are radial glia.…”
Section: Neocortexmentioning
confidence: 99%
“…The participation of the caspase family (previously called the interleukin-1␤ converting enzyme family) of cysteine proteases in programmed cell death (apoptosis) is well established [3][4][5][6]. Apoptosis is required for the development and maintenance of cells in many organ systems, including neuronal cells [7][8][9], cardiac cells [10], and immune cells [11][12][13][14][15]. In addition apoptosis has been implicated in many disease processes, such as Alzheimer's disease [16], Huntingtons disease [17], and amyotrophic lateral sclerosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Berry et al (1983) suggested that the meningeal invasion determines the formation of glial scar, and that immature tissue can retard this invasion. Other authors also suppose that meninx Appearance of glial reactivity in the scenario of cortical maturation in rat Proliferation of cortical neurons (Berry et al, 1964;Berry et al, 1965;Hicks & D'Amato, 1968) First callosal axons cross the midline (Koester & Leary, 1994;Valentino & Jones, 1982) Lesion never provokes glial reaction Glia limitans is complete (Caley & Maxwell, 1970) Severe lesion can heal either without or with glial reaction Lesion provokes glial reaction depending on its size Migration of cortical neurons (Berry et al, 1964;Berry et al, 1965) Gliai reactivity is like in adults Extracellular space of brain tissue decreases significantly (Caley & Maxwell, 1970) Apoptotic elimination of unnecessary cells (Spreafico et al, 1995, Zamenhof & Guthrie, 1995 Perivascular glial sheath appears (Caley & Maxwell, 1970) Beginning glial reaction can be observed GFAP-positivity of glia limitans (Bignami & Dahl, 1974a,b) Transformation of vimentin-positive radial glia into GFAP-positive astrocytes (Cameron & Rakic', 1991;Compston et al, 1997;Pixley & deVellis, 1984) Strong glial reaction can be observed Density of vascular system increases significantly (Caley & Maxwell, 1970;Rowan & Maxwell, 1981) Myelination (Caley & Maxwell, 1970;Compston et al, 1997;Jacobson, 1963;Schonbach et al, 1968) Perivascular glia GFAP-positive (Bignami & Dahl, 1974b) Rapid development of neuropil (Caley & Maxwell, 1970;Eayrs & Goodhead, 1959) Corpus callosum reaches its full extent (Valentino & Jones, 1982) Transformation ofradial glia complete (Cameron & Rakic', 1991;Compston et …”
Section: Results 'Severe' Lesions In Postnatal Animalsmentioning
confidence: 99%